Exposing the magic of design a practitioner's guide to the methods and theory of synthesis - Kolko, Jon. (New York ; Oxford : Oxford University Press, 2011)
This text is immediately relevant, and is more relevant than ever, as we acknowledge and continually reference a feeling of an impending and massive change. Simply, this text is intended to act as a practitioner's guide to exposing the magic of design.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Industrial design -- Psychological aspects; Product design